2022
DOI: 10.1155/2022/5206043
|View full text |Cite
|
Sign up to set email alerts
|

Eye Donation: Awareness, Knowledge, Willingness, and Barriers among Paramedical and Allied Health Science Students at a Tertiary Care Teaching Hospital in South India

Abstract: Background. Visual impairments have physical, emotional, social, and economical consequences and are a crucial element influencing one's quality of life. A total of 1.285 million people are estimated to be visually impaired worldwide of which 39 million are categorised as blind. These figures are startling, given that 80 percent of known vision impairments are either treatable or preventable. Corneal transplants appear to be our best hope for resolving this problem; however, a global shortage of available dono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…25 Our study revealed that 27.6% (n = 13) of the participants were aware of the optimal time for the removal of eyes after death, which is less than that reported by Kacheri et al (67%), Singh et al (41.1%), and Chowdhury et al (69%). 18,21,23 In the current study, barely 43% (n = 20) of the participants were aware of the existence of eye banks in the city. There has been variability in the awareness about the existence of eye banks in various studies.…”
mentioning
confidence: 58%
See 2 more Smart Citations
“…25 Our study revealed that 27.6% (n = 13) of the participants were aware of the optimal time for the removal of eyes after death, which is less than that reported by Kacheri et al (67%), Singh et al (41.1%), and Chowdhury et al (69%). 18,21,23 In the current study, barely 43% (n = 20) of the participants were aware of the existence of eye banks in the city. There has been variability in the awareness about the existence of eye banks in various studies.…”
mentioning
confidence: 58%
“…The knowledge about the donation of eyes after death was poor in our study compared with the study by Kacheri et al (n = 85/150, 56%), Bhandary et al (88%), Singh et al (99.4%), Ronaki et al (80.3%), and Biswas et al (81%). 16,19,21,23,24 Poor knowledge about eye donation was also seen in the study by Lal et al in which only 33% of the participants were aware of eye donation after death. 25 Our study revealed that 27.6% (n = 13) of the participants were aware of the optimal time for the removal of eyes after death, which is less than that reported by Kacheri et al (67%), Singh et al (41.1%), and Chowdhury et al (69%).…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…Various literature studies also reported mass media and public campaigns as the major sources of information. [ 13 15 24 33 34 ] Hence, the requirement for the use of mass media in creating eye donation awareness among students and the general population must be expedited. Furthermore, these eye and organ donation campaigns have been successfully proven in creating awareness in certain states like Tamil Nadu, Andhra Pradesh, and Maharashtra.…”
Section: Discussionmentioning
confidence: 99%
“…People may have the perception that if they had an eye disease, they would have symptoms, and that is not always the case. Hence the need to be aware of health issues through health literacy, which in some cases can be aided by education (Attebo, Mitchell, Cumming, & Smith, 1997;Islam et al, 2015;Kacheri et al, 2022). Shrestha et al (2018) in a study in Nepal using a population-based cross-sectional study between 2008 and 2016 in eight villages concluded that there was a general lack of awareness and knowledge of common eye diseases.…”
Section: Literature Reviewmentioning
confidence: 99%